No evidence of genetic causation between iron and infertility: a Mendelian randomization study - Guo, Liangliang; Yin, Shengnan; Wei, Hongkui; Peng, Jian (Frontiers in Nutrition, 2024)
Background: Observational studies have explored the impact of iron homeostasis on infertility; however, establishing definitive causal relationships remains challenging.This study utilized a two-sample Mendelian randomization approach to investigate the potential causal relationship between iron status and infertility.Four indicators of iron status-serum iron, ferritin, transferrin saturation, and total iron binding capacity, were considered as exposure factors.Infertility was the outcome variable for both men and women. Robust causality was assessed using the primary inverse-variance-weighted method, complemented by three supplementary Mendelian randomization approaches. Sensitivity analyses were performed to enhance the precision and reliability of the results.No statistically significant associations were identified between the four indicators of iron status and infertility. These results remained consistent across multiple Mendelian randomization methodologies.